Enantioselective Alkylation of 2-Oxindoles Catalyzed by a Bifunctional Phase-Transfer Catalyst: Synthesis of (− )-Debromoflustramine B - Connon, Stephen (My University, 2018)
A new bifunctional phase-transfer catalyst that employs hydrogen bonding as a control element was developed to promote efficient enantioselective SN2 reactions for the construction all-carbon quaternary stereocenters in high yield and excellent enantioselectivity (up to 97 % ee) utilizing the alkylation of a malleable oxindole substrate. The utility of the methodology was demonstrated through a concise and highly enantioselective synthesis of (−)-debromoflustramine B.
Keywords: debromoflustramine B; Phase-transfer; Enantioselectivity